Family members' perspectives on the acceptability and impact of a co-facilitated information programme: the EOLAS mental health programme. (9th March 2022) - Higgins, Agnes; Downes, Carmel; Monahan, Mark; Hevey, David; Boyd, Fiona; Cusack, Ned; Gibbons, Patrick
Abstract : Background: Despite the critical role families play in the care and recovery journeys of people who experience enduring mental distress, they are often excluded by the mental health services in the care and decision-making process. International trends in mental health services emphasise promoting a partnership approach between service users, families and practitioners within an ethos of recovery. Objective: This paper evaluated the acceptability of and initial outcomes from a clinician and peer co-led family information programme. Methods: A sequential design was used involving a pre-post survey to assess changes in knowledge, confidence, advocacy, recovery and hope following programme participation and interviews with programme participants. Participants were recruited from mental health services running the information programme. In all, 86 participants completed both pre- and post-surveys, and 15 individuals consented to interviews. Results: Survey findings indicated a statistically significant change in family members' knowledge about mental health issues, recovery attitudes, sense of hope and confidence. In addition, the interviews suggested that the programme had a number of other positive outcomes for family members, including increased communication with members of the mental health team and increased awareness of communication patterns within the family unit. Family members valued the opportunity to share their experiences in a 'safe' place, learn from each other and provide mutual support. Conclusion: The evaluation highlights the importance of developing information programmes in collaboration with family members as well as the strength of a programme that is jointly facilitated by a family member and clinician.